The Giggle book: favorite riddles - Chambliss, Maxie; Calmenson, Stephanie. (Parents Magazine Press, 1987)
An illustrated collection of riddles, such as "What did the mayonnaise say to the refrigerator? Close the door, I'm dressing!".
An illustrated collection of riddles, such as "What did the mayonnaise say to the refrigerator? Close the door, I'm dressing!".
Keywords: Riddles.; Riddles, Juvenile.